2022
DOI: 10.1002/hpm.3506
|View full text |Cite
|
Sign up to set email alerts
|

Violence against health care workers in the workplace in Mozambique – An unrecognised managerial priority

Abstract: Council of Nurse, the World Health Organization and Public Services International and applied in Maputo, Mozambique during 2002. Statistical analysis was carried out with Statistical Package for the Social Sciences 20.0 and WinPepi 11.65. Results: Two hundred and 60 healthcare workers ( HCW ) were selected to participate, 180 agreed, 145 had inclusion criteria and five gave up participating in the study during the consent procedure. Thus, a total of 140 HCW answered the questionnaire. Predominant types of viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The methodological details are described in other article. 3 This questionnaire survey collected self-reported information on VHCW in selected health care units in the 12 months preceding the survey date.…”
Section: Population and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodological details are described in other article. 3 This questionnaire survey collected self-reported information on VHCW in selected health care units in the 12 months preceding the survey date.…”
Section: Population and Methodsmentioning
confidence: 99%
“…In sub-Saharan Africa (SSA), VHCW has been reported from several countries, acknowledging its endemic dimension, the negative impact on health care workers (HCW) and services, a high level of tolerance to non-physical violence and absence of policies to deal with violence, contributing to the underreporting of the problem and its neglect in health workforce planning. 2,3 However, gender aspects of violence have not been properly addressed, remaining the question as to what extent VHCW should be interpreted as gender-based violence (GBV), a global public health problem with a significant prevalence in developing countries. 4,5 This letter revisits data reported previously in this Journal that describe the typology and the perceived impact of VHCW at the health services of the City of Lichinga in Mozambique during 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 In sub-Saharan Africa, studies on VHCW have been reported from several countries, acknowledging the endemic dimension of the phenomenon, the negative impact on the well-being of health care workers (HCW) and their in-service performance, a high level of tolerance to non-physical violence and the absence of policies to deal with workplace violence, contributing to the underreporting of the problem and its neglect in health workforce planning. [5][6][7] Several studies have shown that all forms of VHCW are recognised as a significant issue both by healthcare leaders and workers in Mozambique. 6,7 However, gender aspects of VHCW have not been properly addressed, remaining the question as to what extent it should be interpreted as gender-based violence (GBV), a global public health problem with a significant prevalence in developing countries, [8][9][10] including SSA 11 and Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Several studies have shown that all forms of VHCW are recognised as a significant issue both by healthcare leaders and workers in Mozambique. 6,7 However, gender aspects of VHCW have not been properly addressed, remaining the question as to what extent it should be interpreted as gender-based violence (GBV), a global public health problem with a significant prevalence in developing countries, [8][9][10] including SSA 11 and Mozambique. 12 This report revisits data used for two articles that describe the typology and the perceived impact of VHCW at the Provincial Hospital and at the Health Centre of the City of Lichinga in Mozambique during 2019.…”
Section: Introductionmentioning
confidence: 99%